Toward an inclination to advocate: a discursive study of teachers' stance toward linguistically-responsive pedagogy in online language teacher education. (6th August 2020) - Warren, Amber N.
Abstract: An inclination to advocate is an important orientation for teachers working with emergent bilingual learners; emphasized in both frameworks for teacher education and in teacher education standards. Nevertheless, scholars have only begun to investigate how advocacy is constructed and enacted within online language teacher education coursework designed to promote linguistically responsive pedagogy. This study investigates teacher candidates' orientations to advocacy by examining asynchronous online discussions to understand how candidates' personal stances were interactionally constructed. Analysis drew upon critical discursive psychology for its focus on talk/writing as action-oriented and for its emphasis on the ways that constructs traditionally interpreted as cognitive, such as one's personal beliefs or stance, are made accessible through examining language-in-interaction. Findings demonstrate how candidates oriented to advocacy work as both programmatic and political, while employing specific discursive and conversational features to construct their personal stance within each pattern. This study advances understanding of teacher candidates' 'inclination to advocate' as an essential orientation of linguistically responsive pedagogy and has implications for the planning and design of online language teacher education coursework.